PENGGANTIAN KERUGIAN ATAS PEMBATALAN PEMENANG TENDER PEKERJAAN KONSTRUKSI - Bintang Puwan Permata (Jurnal Indonesia Sosial Teknologi, 2024)
This article aims to determine the legal remedies available to the winner of a construction contract tender when its award is revoked through an invalid administrative court decision. This research is of a normative legal nature and involves a legislative approach and a case approach. The data sources used include primary legal materials related to the procurement of goods and services and principles of civil law, especially those related to compensation for wrongful acts and court decisions. Secondary legal sources were obtained from books and journal articles using a literature review data collection technique. The research findings indicate that a tender winner whose award has been revoked through an invalid administrative court decision can seek compensation by filing a lawsuit in a district court. The compensation obtained may include material compensation, which arises from actual losses suffered by the plaintiff, and immaterial compensation, which is calculated based on the expected profits that could have been obtained if there had been no wrongful act. In the judgment in case number 1/Pdt.G/2017/PN.Lbt, the judge determined that the defendant had committed a wrongful act but awarded the plaintiff only immaterial compensation.